Penerapan Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Indomarco Prismatama Cabang Manyar Rejo - Novia Mega Putri; Novita Rahmawati; Hwihanus Hwihanus (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Employee performance is an important aspect in achieving company goals. Factors such as work discipline and work motivation play a key role in determining the quality of performance. This research focuses on PT. Indomarco Prismatama Manyar Rejo Branch is a consumer goods distribution company in Surabaya, Indonesia. Several problems identified included attendance not being on time, completion of work that was not on target, poor use of work equipment and a lack of discipline in work attitudes. These factors can hinder employee performance and therefore efforts are needed to increase work discipline and motivation. The literature review involves the concepts of management accounting, human resources (HR), work discipline, and work motivation to support an understanding of the factors that influence employee performance. The research method used is descriptive qualitative with a literature study approach. Data was collected through literature studies, including books, scientific articles and research journals as well as through interviews with PT employees. Indomarco Prismatama Manyar Rejo Branch. Data analysis was carried out qualitatively using an inductive method. The research method shows that the application of discipline and work motivation in companies needs to be improved. Employees stated that the implementation of discipline was still not strict enough and work motivation was not optimal. Based on interviews, recommendations for improvement involve clarifying work regulations, consistent supervision, fair rewards and punishments, creating a conducive work environment and employee training.